Coliform density in oyster culture waters and its relationship with environmental factors - Mignani, Luciene; Barbieri, Edison; Marques, Helcio Luis de Almeida; Oliveira, Ana Julia Fernandes Cardoso de (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to evaluate the total and thermotolerant coliform densities in the oyster culture water of Cananeia, SP, Brazil, correlating these densities with environmental variables and tidal variations. Superficial water samples were collected in two tide conditions (spring and neap) from three areas of Cananéia municipality (Mandira, Itapitangui and Cooperostra). The three studied areas showed good conditions for the culture regarding coliform densities. The two tidal conditions differed significantly as to total coliform concentration; however, the same procedure was not performed for thermotolerant coliforms. No correlation was observed between water temperature, pH, and concentrations of total and thermotolerant coliforms. Coliform density was positively correlated with rainfall and negatively correlated with salinity. Spring and neap tides differed significantly as to coliform number. Simple diagnosis of environmental conditions of the crop fields is insufficient to assess water quality of shellfish cultivation. A continuous monitoring program of planted areas is necessary both for the assessment of water quality potential for marine culture and for ensuring safe consumption of seafood, besides constituting an important tool to understand the relationships between contamination and the involved environmental variables.